Educational affordances of mobile social media for language teaching and learning: a chinese teacher's perspective. Issue 4 (4th May 2022) - Xue, Sijia; Churchill, Daniel
Abstract: The educational potential of mobile and social media technologies in combination is becoming increasingly salient with the advance of modern technology. However, there is a dearth in the research on educational use of mobile social media for language learning. This study adopted a qualitative single case study approach to investigate a language teacher's integration of mobile social media in the context of higher education in mainland China, with the aim of exploring educational affordances of mobile social media for language teaching and learning and understanding the relationship between the teacher's technology use and her private theories about technology integration. Data were collected from observation, interviews, as well as documents and artifacts provided by the teacher. Qualitative content analysis was conducted to analyze the data. Five educational affordances of mobile social media emerged from the results, including a motivating environment, resources accessing and sharing, evaluation and feedback offering, administration for learning, and content generation. Results also showed that the teacher's private theories about technology integration changed with her adoption of these affordances. However, such changes did not lead to student-centered technology-based learning designs. Implications for teachers as well as teacher educators are provided. Directions for future research are suggested.